2021
DOI: 10.1108/pr-07-2020-0563
|View full text |Cite
|
Sign up to set email alerts
|

Freelance job search during times of uncertainty: protean career orientation, career competencies and job search

Abstract: PurposeFreelancers are a growing population of working adults with limited to no organizational support. Yet, their strategies to navigate job search, especially in turbulent times, are unknown. To address this gap, the author hypothesized and examined a sequential mediation model whereby freelancer protean career orientation (PCO) influences job search strategies through career competencies (i.e. knowing why, how and with whom to work) and job search self-efficacy (JSSE).Design/methodology/approachData were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…the individuals belief in their ability to perform job search tasks successfully. Drawing on this Ayoobzadeh (2022) proposes a sequential mediation model where the relationship between PCO and job search strategies is mediated by career competencies and JSSE. Career competencies are composed of three components – motivation (knowing why), career-related skills (knowing how) and professional networks (knowing whom).…”
Section: The Sequential Mediation From Pco To Job Search Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…the individuals belief in their ability to perform job search tasks successfully. Drawing on this Ayoobzadeh (2022) proposes a sequential mediation model where the relationship between PCO and job search strategies is mediated by career competencies and JSSE. Career competencies are composed of three components – motivation (knowing why), career-related skills (knowing how) and professional networks (knowing whom).…”
Section: The Sequential Mediation From Pco To Job Search Strategiesmentioning
confidence: 99%
“…The review is based on “Freelance job search during times of uncertainty: protean career orientation, career competencies and job search,” by Ayoobzadeh (2022), published in Personnel Review .…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stringfellow and Shaw (2009), some conceptual articulations of several entrepreneurs’ competencies exist but not essentially vis-à-vis their careers. Hitherto, careers-related studies encapsulate the concept of CC more generally by investigating jointly the “three ways of knowing”, precisely “career motivation and purpose” (knowing-why), “skills and experience” (knowing-how) and “networks and relationships” (knowing-whom) (Ayoobzadeh, 2021; DeFillippi and Arthur, 1994). Whilst competencies have been examined in several contexts, such as expatriate (Dickmann et al , 2018), young professionals (Blokker et al , 2019), employees (Haenggli and Hirschi, 2020; Sultana and Malik, 2019), women managers (Chen et al , 2012) and academics (Beigi et al , 2018; Sherif et al , 2020), not much is understood about their starring function in entrepreneurial careers (Zikic and Ezzedeen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whilst intelligent career theory has been used in other fields such as academia (Beigi et al , 2018; El-Baroudi and Khapova, 2021), executives (Guptill et al , 2018; Lee, 2018), expatriates Cappellen and Janssens (2008) and other professionals (Beigi et al , 2020; Blokker et al , 2019; Haenggli and Hirschi, 2020; Schlosser et al , 2021) and mostly found empirical backing for numerous CC and relevant resources in influencing CS in all its forms, there is a vacuum in the context of entrepreneurs. This especially refers to knowing whom, why and how, which are prominent in the new career literature but are glaringly ignored by most research in the entrepreneurship area (Ayoobzadeh, 2021; Crowley-Henry et al , 2021; Schlosser et al , 2021). Further, despite the intelligent career framework’s (ICF) theoretical appeal and practical applicability, much empirical work continues to focus on CS as measured from an organisational viewpoint.…”
Section: Introductionmentioning
confidence: 99%